protocols.io 2020
DOI: 10.17504/protocols.io.bjjekkje
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella purification v1

Abstract: The United States veterinarian Daniel E Salmon discovered the genus Salmonella. Salmonella is non-spore forming and it may survive without oxygen. This bacterial strain is mainly associated with animals. Salmonella is ubiquitous and may be asymptomatic which has generated great health concern.This bacterium is associated with life threatening diseases among human and animals.Gastroenteritis is one such disease which may resolve itself within five days in healthy individuals.Immuno compromised individuals and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…It has also been reported that the underlying pathophysiology of chronic graft-versus-host disease (GVHD) is similar to autoimmune diseases like scleroderma [ 6 ]. GVHD remains in the differential, but the sites of involvement are usually the GI tract, liver, and skin, with lungs being less commonly involved [ 15 ]. The diagnosis of GPA can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the underlying pathophysiology of chronic graft-versus-host disease (GVHD) is similar to autoimmune diseases like scleroderma [ 6 ]. GVHD remains in the differential, but the sites of involvement are usually the GI tract, liver, and skin, with lungs being less commonly involved [ 15 ]. The diagnosis of GPA can be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The plate was assessed visually for color development and read on a microplate reader at 450 nm. Subsequently, a cut-off point is calculated as the mean of the optical density of the negative controls multiplied by two [13]. The cut-off point was set to 0.268.…”
Section: Spla-lg Direct Elisamentioning
confidence: 99%
“…Table 1 shows that SpLA-LG direct ELISA is a novel immunoassay that examines the binding affinity of a novel hybrid immunoglobulin-binding protein to immunoglobulins from a variety of animal species [10,13]. The authors are not aware of the development of an ELISA using this protein conjugate for immunodetection.…”
Section: Spla-lg Direct Elisamentioning
confidence: 99%
See 2 more Smart Citations